Azithromycin for acute exacerbations of asthma. The AZALEA randomized clinical trial - Johnston,SL; Szigeti,M; Cross,M; Brightling,C; Chaudhuri,R; Harrison,T; Mansur,A; Robison,L; Sattar,Z; Jackson,D; Mallia,P; Wong,E; et al. (JAMA Internal Medicine, 2016)
Importance Guidelines recommend against antibiotic use to treat asthma attacks. A study with telithromycin reported benefit, but adverse reactions limit its use.Objective To determine whether azithromycin added to standard care for asthma attacks in adults results in clinical benefit.Design, Setting, and Participants The Azithromycin Against Placebo in Exacerbations of Asthma (AZALEA) randomized, double-blind, placebo-controlled clinical trial, a United Kingdom–based multicenter study in adults requesting emergency care for acute asthma exacerbations, ran from September 2011 to April 2014. Adults with a history of asthma for more than 6 months were recruited within 48 hours of presentation to medical care with an acute deterioration in asthma control requiring a course of oral and/or systemic corticosteroids.Interventions Azithromycin 500 mg daily or matched placebo for 3 days.Main Outcomes and Measures The primary outcome was diary card symptom score 10 days after randomization, with a hypothesized treatment effect size of −0.3. Secondary outcomes were diary card symptom score, quality-of-life questionnaires, and lung function changes, all between exacerbation and day 10, and time to a 50% reduction in symptom score.Results Of 4582 patients screened at 31 centers, 199 of a planned 380 were randomized within 48 hours of presentation. The major reason for nonrecruitment was receipt of antibiotics (2044 [44.6%] screened patients). Median time from presentation to drug administration was 22 hours (interquartile range, 14-28 hours). Exacerbation characteristics were well balanced across treatment arms and centers. The primary outcome asthma symptom scores were mean (SD), 4.14 (1.38) at exacerbation and 2.09 (1.71) at 10 days for the azithromycin group and 4.18 (1.48) and 2.20 (1.51) for the placebo group, respectively. Using multilevel modeling, there was no significant difference in symptom scores between azithromycin and placebo at day 10 (difference